PACE4 Expression is a Novel Independent Prognostic Factor in Nasopharyngeal Carcinoma - Lin Y; Long H; Tan X; Zhang D; Jiang L (Cancer Management and Research, 2020)
Yunen Lin,1,* Huidong Long,2,* Xiaojun Tan,1,* Donghui Zhang,1 Liwen Jiang1 1Department of Pathology, Affiliated Cancer Hospital & Institute of Guangzhou Medical University, Guangzhou, Guangdong, 510120, People’s Republic of China; 2Department of Medical Oncology, Affiliated Cancer Hospital & Institute of Guangzhou Medical University, Guangzhou, Guangdong, 510095, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huidong LongAffiliated Cancer Hospital  & Institute of Guangzhou Medical University, No. 78 Hengzhi Gang, Guangzhou 510095, People’s Republic of ChinaTel +86-13631319747Email longhuidonggz@163.comBackground: Paired basic amino acid-cleaving enzyme 4 (PACE4) belongs to the family of proprotein convertase and is essential for tumor progression, whereas its role in cancer remains controversial and little is known about its role in nasopharyngeal carcinoma (NPC). The aim of this study was to examine if the expression of PACE4 is a prognostic biomarker for patients with NPC.Methods: Immunofluorescence (IF) and immunohistochemistry (IHC) were used to analyze PACE4 expression in NPC cell line CNE1 and 172 clinicopathologically characterized NPC tissues. The data were analyzed by Chi-square test, Kaplan–Meier plots, and Cox proportional hazards regression model.Results: IF and IHC staining results showed that PACE4 was mainly located in the cytoplasm of NPC cell line (CNE1) and NPC tissues. Expression of PACE4 was observed in 46/172 (26.7%) of NPC tissues. Further analysis showed that expression of PACE4 was positively associated with late N stage, distant metastasis, and late clinical stage (P< 0.05). High expression of PACE4 predicted shorter 5-year overall survival of patients with NPC, especially for the patients in advanced stage (32.7% vs 77.3%, P< 0.001). Furthermore, multivariate analysis showed that PACE4 expression may serve as a potential prognostic factor for NPC.Conclusion: Our results suggest that PACE4 may play a crucial role in tumor progression and may serve as a valuable prognostic biomarker for patients with NPC.Keywords: paired basic amino acid-cleaving enzyme 4, immunohistochemistry, nasopharyngeal carcinoma, overall survival, prognostic biomarker